Pengaruh Penambahan Susu Kedelai dan Protexin terhadap Karakteristik Keju Mozarella Susu Kerbau Rawa - Okta Sriutami; Basuni Hamzah; Merynda Indriyani Syafutri (Seminar Nasional Lahan Suboptimal, 2020)
Sriutami O, Hamzah B, Syafutri MI. 2020. Soy milk and protexin addition effects on characteristics of swamp buffalo milk mozzarella cheese. In: Herlinda et al. (2020.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Swamp buffalo milk has a high fat and protein content, so it has the potential to be processed into mozzarella cheese. Mozarella cheese is a type of soft cheese that has an elastic, soft and stringy texture. An important step in cheese making is the formation of curd. It consists of two ways, namely direct addition of acid and addition of starter culture. The objective of the research was to study the effect of soy milk and lactic acid protexin addition on the physical, chemical, microbiological, and sensory characteristics of swamp buffalo milk mozzarella cheese. This study used a factorial randomized block design with two treatment factors, namely concentration of soy milk (0%, 10%, and 20%) and concentration of protexin (2.5% and 5.0%). The parameters observed included physical (texture), chemical (water and ash content), microbiological, and sensory characteristics using hedonic tests (include texture, overall appearance and aroma). The results showed that concentration of soy milk had significant effects on texture and moisture content, while concentration of protexin had significant  effect on texture. Interaction of soy milk concentration and protexin concentration significantly affected physical (texture) and sensory characteristics (texture and overall appearance) of swamp buffalo milk mozzarella cheese. Based on the highest score of hedonic test (texture and overall appearance), mozarella cheese with 10% of soy milk and 5.0% of protexin addition was the best treatment.